Prediction of weld toe magnification factors for semi-elliptical cracks in single T-butt joints - Hoon, Deborah Jun-Min. (2013)
This work concerns the development of a set of equation(s) to obtain more accurate weld toe magnification factors (Mk) for semi-elliptical cracks in single T-butt joints, and then compared to the Mk values generated by the study done by Lee et al. (2000). Finite element analysis was performed using ABAQUS to generate the stress intensity K values and weld toe magnification Mk values then calculated.